Pengaruh perubahan geometri nosel pada aliran dua fase terhadap kinerja liquid-gas ejector - Rusadi Rusadi; Hadimi Hadimi; Edi Karyadi (Universitas Muhammadiyah Metro, 2022)
Liquid-gas ejector is an energy conversion device capable of flowing air fluid by utilizing water fluid based on the pressure difference between the two fluids without using moving parts. This study aims to determine the effect of changes in nozzle geometry on two-phase flow on the performance of the liquid-gas ejector. The method used is by conducting an experiment whose stages include: determining the nozzle geometry parameter, primary flow rate, and secondary flow rate. Then carry out tests on the installation of liquid-gas ejectors and collect data. The test is done by alternating the nozzle geometry, primary flow rate, and secondary flow rate. Next, analyze the data that has been collected to get the efficiency or performance of the liquid-gas ejector from changes in the nozzle geometry. The results showed that increasing the nozzle geometry tends to cause a decrease in the efficiency and coefficient of the nozzle. The maximum efficiency produced by each nozzle with a geometry of 0.57; 0.64; 0.71; 0.79 and 0.86 respectively were 24.33%, 23.43%, 8.19%, 16.21%, and 7.96%. While the nozzle coefficients are 0.94, respectively; 0.81; 0.59; 071; and 0.59.